The Characteristics of Standard Instruments for Early Detection of Terrorism in the Name of Jihad in High School Students (Journal of Research and Educational Research Evaluation, 2022)
Radical religious understanding has become a horrendous phenomenon, because religion, especially Islam, does not teach radicalism or even terrorism. This study aims to (1) analyze the design of instruments for early detection, (2) analyze the characteristics of the standard’s instrument in the form of the level of instrument validity and (3) analyze the level of reliability on the instrument for early detection of terrorism in the name of jihad in students of SMA Negeri 2 Semarang. This research uses descriptive qualitative and quantitative research. The content validity of the instrument was tested by 3 experts. The statement items developed were tested on 30 respondents (small class) and 145 respondents (large class). Data was collected using interview techniques, documentation and questionnaires. The results of this study produced 45 standard instrument items for early detection of terrorism in the name of jihad in the form of a Likert scale of 1-4 and presented online using a google form. The results of validation by experts are that there are 14 items that are declared invalid or have an Aiken V index value of less than 0.3 so that these items must be discarded. The non-test instrument has an interrater reliability coefficient, a small class trial, and a large class trial, respectively, which is 0.88; 0.92; 0.91. There are 17 items that are invalid or less than the correlation coefficient rcount in the small class trial. Based on the large class trial, the final results of the valid items were 45 items with an r-count value greater than 0.1362 and a non-negative value. The results of the KMO in the field trial were 0.803 so that the instrument items could be analyzed further. The instrument is formed into 12 factors. The instrument developed is constructivly valid because it is able to explain the overall variation in the terrorism early detection instrument of 66.79%. The conclusion from this study is that the the non-test instrument in the form of a Likert scale. The characteristics standard’s instruments of early detection for terrorism in the name of jihad is constructivly valid and reliable.